Fatigue life assessment and damage investigation of centrifugal pump runner. (June 2021) - Xie, Zhanshan; Shi, Weidong; Tian, Qian; Zheng, Yuan; Tan, Linwei
Abstract: Damage investigation based on the Miner theory principle is elaborated in this paper. And a new method to eliminate the secondary load spectrum is presented based on the existing load spectrum processing methods. With the aid of this method, the statistical work of the average stress and amplitude of load spectrum at the maximum stress point in the runner structure field is completed, meanwhile, the damage degree of the runner under two-dimensional stress and the life of the runner are calculated separately. According to the maximum stress position of the runner where is prone to occur, the crack is set. Based on the simulation analysis results and the relationship between the strength factor and the integral factor of the crack, the elastoplastic state of the runner crack is identified and the influence of the local crack of the runner on the strength of the runner is clarified.